Bangladesh SHAHAR Dinajpur Baseline Survey, 2002-2003 - International Food Policy Research Institute (International Food Policy Research Institute, 2009)
The SHAHAR (Supporting Household Activities for Health, Assets and Revenue) project aims to increase incomes and improve unhygienic environments and sanitation conditions in poor urban communities, including slums, in major selected secondary cities in Bangladesh. Using relevant indicators namely socioeconomic; health and hygiene; nutrition and diet; and governance and social institutions the project provides insight into the livelihood conditions and the livelihood security of these slum households. The SHAHAR baseline survey was conducted in July to August, 2002 in slum (basti) communities in Dinajpur. The SHAHAR census survey suggested that only 52 percent of households had children under 5 years of age; doubling the sample size would ensure that the final sample would have at least this many households with children under 5 years of age. This gave an estimated sample size of 271 * 2 = 542. As slum dwellers are assumed to be highly mobile, and the losses would increase over the year between round I in July – August, 2002 and round III a year later, a substantial reserve was added to the sample, as well as some allowance for refusal or other non-response, for a final total of 614 households. The field survey was carried out by two teams, each consisting of three male and female pairs and a supervisor. One pair interviewed one household at a time, with the female interviewer interviewing the main female member of the household and collecting information on household composition, migration and education; training; savings; loans; food consumption; household food security; health; anthropometry and childcare; environment, water and sanitation; shocks and coping strategies; social capital; crime, violence, physical security; governance; and women’s status. The male interviewer interviewed the main male member of the household asking questions on language, religion, and migration; training; employment; transfers, social assistance and other income; household assets; land ownership and tenure; urban agriculture; savings; loans; housing; non food expenditure; shocks and coping strategies; social capital; crime, violence and physical security; and governance. The pairs on each team worked together to cover three households per day and the 614 households surveyed in approximately 39 days in July to August, 2002 in Dinajpur. The first baseline data of SHAHAR project, 2000 is also available from IFPRI’s Dataverse at https://doi.org/10.7910/DVN/WUDIJU.